As regras de subcapitalização no Brasil: distanciamentos e proximidades com os juros sobre o capital próprio e os preços de transferência - Drezza, Lia Barsi (2013)
This study assesses the impact of the normative statement contained in Articles 24 and 25 of Law No. 12.249/2010 Brazil s "thin capitalization rules" in view of a series of other laws currently in effect that regulate the same issues, namely, the remittance of interest abroad by entities affiliated with enterprises headquartered in tax havens or in countries featuring low-tax regimes. The analysis seeks to highlight the conflicts that can arise from regulation by different laws of the same legal facts, as a means to prevent the occurrence of double taxation by the tax authorities